In vivo protein-based biosensors: seeing metabolism in real time. Issue 1 (January 2023) - Alexandrov, Kirill; Vickers, Claudia E.
Abstract : Biological homeostasis is a dynamic and elastic equilibrium of countless interlinked biochemical reactions. A key goal of life sciences is to understand these dynamics; bioengineers seek to reconfigure such networks. Both goals require the ability to monitor the concentration of individual intracellular metabolites with sufficient spatiotemporal resolution. To achieve this, a range of protein or protein/DNA signalling circuits with optical readouts have been constructed. Protein biosensors can provide quantitative information at subsecond temporal and suborganelle spatial resolution. However, their construction is fraught with difficulties related to integrating the affinity- and selectivity-endowing components with the signal reporters. We argue that development of efficient approaches for construction of chemically induced dimerisation systems and reporter domains with large dynamic ranges will solve these problems. Highlights: Biosensors enable quantification of analytes of choice inside living cells. Protein biosensors can transform the way we monitor and engineer metabolism. The key challenges are to develop biosensors with large dynamic range and tuneable specificity. Ultimately, we seek to democratise this technology so that it is readily available to the scientific community.